Ideology at Play : The English Subtitling of the Weekly Thai Prime Ministerial Addresses - Phanthaphoommee, Narongdej (Critical New Literacies: The Praxis of English Language Teaching and Learning, 2024)
The book explores the complex relationship between ideology, language, and cultural nuances during subtitling, illuminating the translators' strategic decisions in capturing the depth of Thai political speech. It exposes the nuanced ways in which language can affect the comprehension of political messages and shape perceptions by drawing on an abundance of examples. Ideology at Play looks at the problems and opportunities that come up when these famous speeches are translated. It covers linguistic subtleties, cultural sensitivities, and the complicated relationship between language and politics. It gives new ideas about how ideology shows up in translated texts.